EFEKTIFITAS GAME MARBEL MUSLIM KIDS PADA MATA PELAJARAN PAI UNTUK MENINGKATKAN PEMBELAJARAN YANG MENYENANGKAN - Kholishoh Nur Aini; Abdul Muhid (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
The use of technology and information technology produces educational games. Islamic Education (PAI) learning media so as not to be boring and become a fun learning by using educational games in the form of Game Marbel Muslim Kids This research uses this type of literature research (library research) which is research that relies on literature materials as a source of information to answer the problem of the effectiveness of using The Marbel Muslim Kids Game in PAI lessons to be able to create the concept of literature. in learning. This research method is descriptive, to describe the effectiveness of the Marbel Muslim Kids Game in PAI subjects to promote fun learning. The use of media on interactive learning can increase the effectiveness of learning, learners understand more easily, there is fun learning, and interesting for learners and also supported by data and learning approaches that are expected practically and theoretically. The use of game media in this case Marbel Muslim Kids Game is an educational game, a game that contains learning materials supporting Islamic Education (PAI) lessons in the learning process has a very large role for understanding the material delivered by educators to their learners.